A Case of Ocular Myasthenia Gravis Presenting as Double Depressor Palsy - Lee, Kwanbok (The Korean Ophthalmological Society, 2014)
A 65-year-old man who had been experiencing diplopia in front and down gaze for 15 days visited our hospital. Hypertropia was noted in the patient's left eye, and limitation of depression was found in the adduction, primary gaze, and abduction. Brain magnetic resonance imaging showed no remarkable findings. Two weeks after the first visit, the patient complained of ptosis in the left eye. An ice test was performed and the ptosis was resolved after the test. Then, anti-acetylcholine receptor binding antibody levels were checked and found to be slightly elevated. We prescribed methylprednisolone per os 24 mg for 2 weeks, and his symptoms improved after the 2-week treatment. Five weeks after his first visit, the patient showed an ortho result in the alternate prism cover test and normal ocular movements. This may be the first case in which ocular myasthenia gravis presented as double depressor palsy, and in such cases, the possibility of ocular myasthenia gravis should be considered to rule out double depressor palsy.